Unraveling Communication Barriers among Apathetic Students in Media Writing - Surendra, Gilang; Laily, Hamidah Izzatu; Telaumbanua, Yohannes (ABEC Indonesia, 2024)
This qualitative research explores the communication barriers that contribute to apathy among students in the"Writing for Media" course at the English Department of Politeknik Negeri Padang. Utilizing in-depth interviews anddirect observations, the study identifies the factors causing disengagement and examines how ineffective communicationdynamics exacerbate apathy. By analyzing the experiences of apathetic students, the research aims to shed light on theunderlying issues hindering their academic participation. Targeted findings will provide valuable insights for educators,facilitating the development of targeted strategies to enhance engagement and improve the learning environment.Furthermore, this research aspires to contribute to the ongoing discourse on educational effectiveness by deepening ourunderstanding of how communication challenges affect student motivation and learning outcomes. By focusing on therelationship between communication barriers and apathy, this study not only seeks to improve academic performance butalso to design inclusive educational strategies that promote student motivation, ultimately leading to a more dynamicclassroom experience.